CALAGEM SUPERFICIAL COM CALCÁRIO CALCÍTICO E DOLOMÍTICO DE DIFERENTES GRANOLUMETRIAS EM SISTEMA PLANTIO DIRETO - Rodrighero, Maik Barbosa (2012)
To control soil acidity in no-till systems, lime is broadcast on the surface without incorporation. In order to test the hypothesis that the source and particle size of the corrective influence the soil reaction and crop response to lime on the surface in no-till system, two experiments were conducted in Tibagi (PR), one in clayey Oxisol and another in sandy Litholic Neosol. A randomized complete block design was used in a factorial 2 × 2 × 4 with three replications, in each experiment. The treatments consisted of four rates of lime on the surface, estimated to raise the base saturation of the topsoil (0-20 cm), at 50, 70 and 90%; two sources of lime were used, calcitic and dolomitic,and two ranges of lime material effective calcium carbonate equivalent (ECCE), range B (ECCE 60-75%) and range D (ECCE > 90%). In both experiments, the lime was applied on the soil surface in August 2010. During the spring-summer season in 2010- 11 and 2011-12, corn and soybean were grown on the clayey soil, and soybean and corn on the sandy soil, respectively. After 12 months of liming, soil chemical analyses were performed in samples taken at the 0-5, 5-10, 10-20, 20-40, and 40-60 cm depths. Leaf samples of corn and soybean were taken during crop flowering, in the second year of cultivation, for foliar diagnosis. Grain yields of corn and soybean, in both experiments,were evaluated in two years, after the physiological maturity, and grain moisture was corrected to 130 g kg-1. Surface application of lime in both soils, after 12 months, promoted amelioration of soil acidity mainly in the 0-5 cm layer and, to a lesser extent in the 5-10 cm, regardless of the source and range of lime ECCE. Calcitic lime showed a stronger reaction than dolomitic lime in the soil surface layers. The extraction with cation exchange resin overestimated the exchangeable Ca and Mg content in relation to the 0.1 mol L-1 KCl solution when coarser grain size lime was applied on the surface. Surface liming increased the Ca-leaf content, especially with the use of calcitic lime, and Mg-leaf content mainly with the use of dolomitic limestone, and reduced Mn and Zn contents in the leaves, regardless of the source of lime, in the corn and soybean crops. Grain yields of corn and soybean in clayey Oxisol and corn in sandy Litholic Neosol were increased with the lime rates, but were not affected by sources and ECCE ranges of material lime. Surface application of lime in soils under no-till was proved of fundamental importance to maximize crop grain yield, regardless of the lime source being calcitic or dolomitic, or the ECCE range, B or D of the material lime.